2003
DOI: 10.1046/j.1095-8339.2003.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf structure of Syzygium spp. (Myrtaceae) in relation to site affinity within a tropical rain forest

Abstract: This study examined four species of Syzygium (S. firmum, S. makul, S. operculatum, S. rubicundum) Myrtaceae, a tree genus that dominates the canopy of rain forests of south‐west Sri Lanka. Syzygium spp. occupy differing habitats with relation to succession and forest topography. We examined differences in leaf morphology and physiology in response to amount of shade, an important environmental variable affecting Syzygium distribution within the forest. To study change in leaf structure and physiology, environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…Trends appear related to size of disturbance, stature of the forest, topographic position, and underlying geology and soil-weathering environment. Previous studies have demonstrated tree species differences in shade tolerance (Ashton, 1995;Ashton et al, 1995Ashton et al, , 2005Gamage et al, 2003); response to soil nutrition (Gunatilleke et al, 1996(Gunatilleke et al, , 1997Singhakumara et al, 2003) and aversion to drought (Ashton et al, 2005). The results from this study provide a stronger context for work conducted on Sri Lankan mixed dipterocarp forest on forest regeneration.…”
Section: Discussionmentioning
confidence: 49%
“…Trends appear related to size of disturbance, stature of the forest, topographic position, and underlying geology and soil-weathering environment. Previous studies have demonstrated tree species differences in shade tolerance (Ashton, 1995;Ashton et al, 1995Ashton et al, , 2005Gamage et al, 2003); response to soil nutrition (Gunatilleke et al, 1996(Gunatilleke et al, , 1997Singhakumara et al, 2003) and aversion to drought (Ashton et al, 2005). The results from this study provide a stronger context for work conducted on Sri Lankan mixed dipterocarp forest on forest regeneration.…”
Section: Discussionmentioning
confidence: 49%
“…1), which together with increased stomatal density gives it the distinguishing marks of a heliophilous plant (Lüttge et al 1997). The further plants get from the shadow condition the more these aspects are enhanced (Gamage et al 2003). HS supposed higher efficiency for light did not led to any significantly different performance in terms of net photosynthesis (Pn) in respect of H. At 25°C HS shows higher stomatal conductance (g s ) compared to H. Pn (net photosynthesis) and E (evapotranspiration) are inextricably linked through g s (Miyazawa et al 2006); g s responds to Ci concentration such that the ratio of ambient CO 2 (Ca) and Ci remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…Chazdon and Kaufmann (1993) found that while two species of rain forest shrubs adapted similarly in terms of leaf structure (thicker leaves, higher leaf mass per area) under high light, their physiological response to higher light levels differed. Several genera such as Shorea, Entandrophragma, Syzygium, and Macaranga have exhibited different responses to light levels, thereby enabling these species to divide the available light and co-exist within the forest (Ashton and Berlyn, 1992;Ashton et al, 1995;Davies et al, 1998;Gamage et al, 2003;Hall et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Three principal environmental gradients -light, precipitation, soil nutrients -have been studied extensively in tropical forest ecosystems worldwide, elucidating how species interactions with various environmental conditions determine forest composition, diversity, structure, and succession (Ashton and Berlyn, 1992;Wright, 1992;Ashton et al, 1995;Gamage et al, 2003;Hall et al, 2003;Givnish et al, 2004;Ashton et al, 2005). Tree species adjust physiological traits, such as net photosynthetic capacity, transpiration and growth rates, and shoot:root ratios, in response to different light and soil moisture regimes (Bazzaz, 1979).…”
Section: Introductionmentioning
confidence: 99%